Specific features of Infusion Therapy in Bariatric Surgery - M. I. Neymark; S. V. Zhilin (Вестник анестезиологии и реаниматологии)
The objective: to determine principles of intraoperative infusion therapy in patients with morbid obesity under the control of volemic status.Methods: a prospective randomized study was conducted in 60 patients with BMI of 45.57 (40.01; 48.65) kg/m2 who underwent laparoscopic gastric resection under combined anesthesia based on low-flow desflurane inhalation in combination with prolonged epidural analgesia with ropivacaine. Patients were allowed to consume 200 ml of clear liquid 3 hours before the surgery, and solid foods 6 hours before surgery. Patients were divided into 2 groups (n = 30) depending on the composition of infusion therapy: colloids (gelatin solution) were used in Group 1 with balanced crystalloids in a ratio of 1:1-1.5, balanced crystalloid solutions were used in Group 2. The following parameters were studied: hemodynamics, water sector distribution index (IRVS), hemoglobin, hematocrit, potassium ions, sodium, creatinine, lactate, and CBS. A PLR test was performed intraoperatively.Results. It was revealed that the patients had an uneven distribution between water sectors with shortage of fluid in the intravascular bed, as evidenced by a positive PLR test, as well as low IRVS. When conducting targeted infusion therapy in Group 1, a smaller volume of infusion solutions was used, however, that made it possible to achieve stabilization of hemodynamic parameters due to redistribution of water sectors, which was also evidenced by changes in laboratory parameters.Conclusion. Obese patients have intravascular fluid deficiency due to uneven distribution between water sectors. The inclusion of a colloidal plasma substitute to the infusion therapy contributes to the elimination of hypovolemia and reduces the volume of transfused media.